Re-visiting the Frank-Starling nexus. (January 2021) - Han, June-Chiew; Loiselle, Denis; Taberner, Andrew; Tran, Kenneth
Abstract: Well over a century ago, Otto Frank, working at Carl Ludwig's Institute of Physiology in Munich, studying the isolated, blood-perfused, frog heart preparation, demonstrated that there are two distinct pressure-volume relations in the heart: one for isovolumic twitches and a second (located inferiorly) for afterloaded twitches. Whereas Starling, working at UCL two decades later, referenced Frank's publication (to the extent of re-printing its seminal Figure), he appeared not to have tested Frank's finding. Hence, he remained silent with respect to Franks' contention that cardiac pressure-volume relations are contraction-mode-dependent. Instead, he concluded that " The energy of contraction, however measured, is a function of the length of the muscle fibre " - a conclusion that has become known (at least in the English-speaking world) as ' Starling's Law of the Heart' . This provides us with at least three conundra: (i) why did Starling present only one pressure-volume relation whereas Frank had previously found two, (ii) why, then, do we speak of The Frank-Starling relation, and (iii) how did Frank become largely forgotten for twelve decades among English speakers? This review will attempt to address and comment on these conundra.